THE EFFECT OF RECEIVABLES TURNOVER AND CURRENT RATIO ON PROFITABILITY IN MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2021-2023 - Yunita Delfin Sihombing; Kristi Endah Ndilosa Ginting; Mella Yunita (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
Profitability is a fundamental component in reviewing the success of management in managing the company's financial performance. The purpose of this study is to examine whether the receivables turnover and current ratio (CR) have an effect on profitability. The population of this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample of this study is 25 companies that are determined through a quantitative approach method using data in numerical form which is collected through secondary data processing, namely financial statements that are published and can be accessed through the IDX Data collection technique from the IDX website, namely www.idx.co.id. Through the results of the study, it was found that the turnover of receivables does not have a significant influence on profitability and CR has a significant influence on profitability for Manufacturing Companies listed on the IDX in 2021-2023.